2017
DOI: 10.1038/ncomms14726
|View full text |Cite
|
Sign up to set email alerts
|

Pre-plaque conformational changes in Alzheimer’s disease-linked Aβ and APP

Abstract: Reducing levels of the aggregation-prone Aβ peptide that accumulates in the brain with Alzheimer's disease (AD) has been a major target of experimental therapies. An alternative approach may be to stabilize the physiological conformation of Aβ. To date, the physiological state of Aβ in brain remains unclear, since the available methods used to process brain tissue for determination of Aβ aggregate conformation can in themselves alter the structure and/or composition of the aggregates. Here, using synchrotron-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 38 publications
3
72
0
Order By: Relevance
“…For the experiment, as a negative control for Aβ, we used APP knock‐out neurons derived from mice which lack the APP gene and therefore do not produce Aβ proteins 30. As another control, we used wild‐type mouse neurons which have the mouse APP gene and produce mouse Aβ which does not aggregate,22 these genetic modifications allowed us to study Aβ specific structural changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the experiment, as a negative control for Aβ, we used APP knock‐out neurons derived from mice which lack the APP gene and therefore do not produce Aβ proteins 30. As another control, we used wild‐type mouse neurons which have the mouse APP gene and produce mouse Aβ which does not aggregate,22 these genetic modifications allowed us to study Aβ specific structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…Primary neurons were seeded directly on 13 mm diameter and 1 mm thick CaF 2 spectrophotometric windows (Eksma Optics, Lithuania) and grown for 19 days. To avoid artificial β‐sheet formation, neurons were fixed with 4% paraformaldehyde in phosphate buffer saline for 15 min washed with 20 × 10 −3 m phosphate buffer (PB) and stored at −80 °C until measurements 22. µFTIR spectromicroscopy was performed at the SMIS beamline of the SOLEIL synchrotron (France) using a Thermo Fisher Scientific Continuum XL FTIR microscope through a 32× magnification, 0.65 NA Schwarzschild objective.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the molecular events leading to the formation of these species are supposed to appear 10–20 years before the symptoms become evident . Studies aimed at unraveling the relationship between structure and neurotoxicity of misfolded oligomers are thus pivotal in gaining insights into the pathological process, as well as in designing novel diagnostic and therapeutic strategies tuned toward the earliest and presymptomatic stages of the disease …”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the physiological conformation of Aβ is altered before the formation of amyloid plaques, and that the Aβ peptide initially exists as a β-sheet rich tetramer. These results suggests a novel therapeutic approach, where stabilization of the tetramer, similar to that of transthyretin (TTR) in transthyretin amyloidosis, could inhibit the oligomerization and toxic effects of Aβ [121].…”
Section: Introductionmentioning
confidence: 99%